Juvenility and Vegetative Phase Transition in Tropical/Subtropical Tree Crops - Ahsan, Muhammad Umair; Hayward, Alice; Irihimovitch, Vered; Fletcher, Stephen; Tanurdzic, Milos; Pocock, Alexander; Beveridge, Christine Anne; Mitter, Neena (Frontiers in Plant Science, 2019)
In plants, vegetative to reproductive phase transition is regulated by the sequential activity of two microRNAs: miR156 and miR172. A decline in miR156 and increase in miR172 abundance is associated with phase transition. There is very limited information on phase transition in economically important horticultural tree crops, which have a significantly long vegetative phase affecting fruit bearing. Here we profiled various molecular cues known to be involved in phase transition and flowering, including the microRNAs miR156 and miR172, in three horticultural tree crops avocado (Persea americana), mango (Mangifera indica) and macadamia (Macadamia integrifolia). We observed that miR156 expression decreases as these trees age and can potentially be used as a juvenility marker. Consistent with findings in annual plants, we also observed conserved regulation of the miR156-SPL4 regulatory module in these genetically distant tree crops, suggesting that this pathway may play a highly conserved role in vegetative identity. Meanwhile, the abundance of miR172 and its target AP2-like genes, as well as the accumulation level of SPL9 transcripts, were not related with plant age in these crops except in avocado where miR172 expression increased steadily. Finally, we demonstrate that various floral genes, including AP1 and SOC1 were upregulated in the reproductive phase and can be used as potential markers for the reproductive phase transition. Overall, this study provides an insight into the molecular associations of juvenility and phase transition in horticultural trees where crop breeding and improvement is encumbered by long juvenile phases.